The presence of a conjugative Gram-positive Tn2009 in gram-negative commensal bacteria - Ojo, Kayode K. (2018)
Objectives: To determine whether mef(A)-msr(D) and tet(M) genes are linked in representative Gramnegative isolates and/or transferred together during conjugation. To molecularly characterize the Acinetobacter junii element and compare the structure and sequence with the non-conjugative Streptococcus pneumoniae Tn2009 element. Methods: PCR assays, DNA–DNA hybridization and sequencing of PCR products were used. Nucleotide sequences were determined at the integration site of the mef(A) element into Tn916 and upstream and downstream flanking regions of the element. Results:Atotal of 10 mef(A)-msr(D)- and tet(M)-positive isolates carried conjugative element(s). The A. junii Tn2009 element was indistinguishable from S. pneumoniae Tn2009. The region upstream of the A. junii Tn2009 contained an orf that was 89–91% identical to an S. pneumoniae spr1206 gene found upstream of the streptococcal Tn2009. In the A. junii, the spr1206 gene was separated by 67 bp from the end of the Tn2009, while 29 bp were found separating spr1206 from the streptococcal Tn2009. The 1201 bp downstream A. junii sequences included 913 unique sequences. Conclusions: A total of 10 different Gram-negative genera were found to carry the tet(M) genes, including the first description in three genera (Citrobacter, Proteus and Stenotrophomonas). All isolates were able to transfer the genes into ‡1 recipient with macrolide selection. Over 3000 bp were sequenced on each side of the insertion mef junction region in the A. junii and were indistinguishable from the streptococcal Tn2009. The A. junii Tn2009 element was flanked by an S. pneumoniae gene upstream and a unique sequence downstream, suggesting that the A. junii Tn2009 could be part of a larger element.